Śląskość w narracji wspomnieniowej Floriana Śmiei - Filip, Grażyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
The aim of the linguistic analyses provided in the article is to answer the question: to what degree and through which lexical markers the Silesian parentage of Florian Śmieja is reflected in his narrative memoirs. The third volume of "Zbliżenia i kontakty" with the first chapter entitled "Gniazdo" (i.e. hearth), describing Silesian childhood and youth of Śmieja, is considered the subject of the analysis. Link with the place of birth and strength drawn from such relationship is closely related to the sociological concept of little homeland (regionalism) that functions in the field of linguistics as well. The article partially reconstructs the linguistic depiction of “Silesianity” recorded in the idiolect of Florian Śmieja. The term "Silesianity", from the linguistic point of view, is treated as an effect of word formation process that resulted in the abstract specific name derived from the adjective "Silesian". In order to select the examples discussed in the article all the mentioned semantic aspects of the derivative core of "Silesian", understood as "related to the Silesia region, originating in Silesia, typical for Silesia", were taken into consideration. The presented observations use the optimal definition of "linguistic picture of the world". According to the definition, linguistic picture of the world is considered an interpretation of reality, embedded in language but verbalized in a number of variants. Such interpretation can be described via both a set of explicit expressions recorded in language and implied opinions of the world recorded at the level of social knowledge. From this perspective, the image of "Silesianity" in the prose of Florian Śmieja is realized through few essential constituents: 1. geographical names, 2. characters of Silesian people, 3. regional lexical items, 4. Silesian tradition. The "Silesianity" in the memoirs by Florian Śmieja refers to the region marked by towns important for him during his childhood and youth. The excerpt of the language picture of "Silesianity", reconstructed on the basis of "Gniazdo", does not overwhelm its reader with the frequent usage of regional dialect incomprehensible for foreigners. The author is concerned with wide audience and thus implements dialectical lexical features in his narration either in context that provides necessary explanation, or together with commonly known Polish synonyms.
Silesianity in the narrative memoirs of Florian Śmieja
Keywords: Śmieja Florian; śląskość; dialekt śląski; pamiętniki polskie - XX w.